Evaluation of diffusive gradients in thin films technique (DGT) for measuring Al, Cd, Co, Cu, Mn, Ni, and Zn in Amazonian rivers - Marques Yabuki, Lauren Nozomi [UNESP]; Colaco, Camila Destro [UNESP]; Menegario, Amauri Antonio [UNESP]; Domingos, Roberto Naves [UNESP]; Kiang, Chang Hung [UNESP]; Pascoaloto, Domitila (Springer, 2014)
Studies concerning the lability and bioavailability of trace metals have played a prominent role in the search for contamination of water resources. This work describes the first application yet of the diffusive gradients in thin films technique (DGT) to the determination of the fraction of free plus labile metals in waters from the Amazon Basin. Due to the complexity of the use of DGT for samples with low ionic strength and high organic matter content (characteristic of Amazonian rivers), a new analytical procedure was developed. The method is based on the determinations of apparent diffusion coefficients (D-ap) in the laboratory, by performing deployments in samples collected in the corresponding sites of study. The D-ap thereby determined is then used for in situ measurements. The suitability of the proposed approach for determination of labile Al, Cd, Co, Cu, Mn, Ni, and Zn in the Amazon River and Rio Negro (English: Black River) was evaluated. Except for Co, Mn (in a deployment at Rio Negro), Ni and Zn (in a deployment at Amazon River), labile in situ measurements were lower or similar to dissolved concentrations, indicating suitability of the proposed approach.
Keywords: DGT; Amazon Basin; Lability; Trace metals